“Drip Irrigation: Cultivating Sustainability through Efficient Water Management” - Dr. Pardeep Malik (Eduzone: International Peer Reviewed/Refereed Multidisciplinary Journal, 2018)
One beneath the surface irrigation practice is drip irrigation, also referred to as trickling irrigation. It involves providing water regularly to crops using micro emitters at the root area, soaking only a fraction of soil's surface area and depth. The idea behind drip irrigation is to provide the crops' roots with enough moisture to prevent water stress.The most effective method for providing water and nutrients to crops is drip irrigation. Each plant gets exactly the amount of water and nutrients it requires at the precise moment for optimum growth by being delivered straight to the root zone of the plant. Water supplies were reduced as the result of the rapid urbanization & population rise.